The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1002/bit.260390511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactate concentration on hybridoma culture in lactate‐controlled fed‐batch operation

Abstract: To investigate the effects of lactate on cell growth and antibody production, a new method of maintaining the lactate concentration constant in a fed-batch culture is described. When the pH was initially adjusted by sodium hydroxide, the specific growth rate decreased and specific death rate increased with an increase of lactate concentration. To investigate whether the inhibition was due to the lactate concentration itself or to the osmotic pressure, the effect of the osmotic pressure adjusted by sodium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 23 publications
3
71
1
Order By: Relevance
“…The results also showed that CD147 silencing resulted in an increase of the intracellular lactate concentration in pancreatic cancer cells. The increase of lactate concentration may inhibit the cell growth, since lactate has been demonstrated to decrease pyruvate reduction to lactate by inhibition of (LDH) (39). However, the present results did not show that the increase of lactate concentration inhibited the proliferation in Panc-1 cells (data not shown), and we will investigate the mechanism in the future.…”
Section: Discussioncontrasting
confidence: 63%
“…The results also showed that CD147 silencing resulted in an increase of the intracellular lactate concentration in pancreatic cancer cells. The increase of lactate concentration may inhibit the cell growth, since lactate has been demonstrated to decrease pyruvate reduction to lactate by inhibition of (LDH) (39). However, the present results did not show that the increase of lactate concentration inhibited the proliferation in Panc-1 cells (data not shown), and we will investigate the mechanism in the future.…”
Section: Discussioncontrasting
confidence: 63%
“…The change in cell density is presented as the mean of two independent experiments. The specific growth rate was calculated from the total cell density and incubation time during 72 h-culture Omasa et al, 1992 .…”
Section: Quantification Of Uv-a-induced Intracellular Rosmentioning
confidence: 99%
“…They are well known inhibitors of both cellular growth and productivity, with detrimental effects reported for lactate levels exceeding 20 mM and ammonia concentrations as low as 2-3 mM (Cruz et al, 2000;Glacken, 1986;Hassell et al, 1991;Omasa et al, 1992a;Ozturk et al, 1992). Moreover, these metabolites were shown to adversely affect product quality, most notablybyalteringtheglycosylationpattern (Andersen and Goochee, 1995;Borys et al, 1994;Chen and Harcum, 2006;Gawlitzek et al, 1998;Grammatikos et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…At the process level, the apparent deregulation of glucose and glutamine uptake rates when these nutrients are present in excess has led to the implementation of controlled feeding strategies to maintain low but non-limiting levels of the main nutrient concentrations (Europa et al, 2000;Gambhir et al, 1999;Kurokawa et al, 1994;Lee et al, 2003;Haggstrom, 1992, 1994;Omasa et al, 1992aOmasa et al, , 1992bSiegwart et al, 1999;Zhou et al, 1995). Such strategies have proven effective at reducing the overall yield of lactate on glucose, but require on-line monitoring of nutrient concentrations and automatic feed rate adjustment during the culture.…”
Section: Introductionmentioning
confidence: 99%